2020
DOI: 10.1007/s11615-020-00230-w
|View full text |Cite
|
Sign up to set email alerts
|

The Existence of Courts and Parliaments in Regional Organizations: A Case of Democratic Control?

Abstract: Why do states design regional organizations with courts and parliaments? Is it indeed the case that states establish them because they expect these organs to exert some kind of democratic control over executives? Undoubtedly, this is an important question given that politicians and political scientists alike regularly lament the lack of democratic control of many international organizations. We tackle this question empirically. Based on an original data set of 72 regional organizations and by using simple logi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…Studies support secondary or, ultimately, mixed sources of informatio COIL project led by Koremenos and the Issue Correlates of War (ICOW) led Pevehouse research team were observed to be significantly recurrent. On the othe other researchers offer novel dataset contributions [64,80,86,89,90]. These cases ill the way in which the examined discipline was built.…”
Section: Methodological Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies support secondary or, ultimately, mixed sources of informatio COIL project led by Koremenos and the Issue Correlates of War (ICOW) led Pevehouse research team were observed to be significantly recurrent. On the othe other researchers offer novel dataset contributions [64,80,86,89,90]. These cases ill the way in which the examined discipline was built.…”
Section: Methodological Approachmentioning
confidence: 99%
“…As they are deeply rooted in economics, these econometric models were certainly not accidentally used in the examined rationalist empirical works. Both logistic regression and ordinary least squares (OLS) methods were the second most frequently used methods in the examined literature [63,77,80,86,87]. Third, a chi-square test and a cross-tabulation analysis were each performed once each [79,83].…”
Section: Methodological Approachmentioning
confidence: 99%
See 1 more Smart Citation